Determination of IL17 Plasma Levels and IL-17A gene Polymorphisms in Patients with Allergic Rhinitis - Mohammed D. D. AL-Beagy1 , Thanaa M. Jouda2 , Safaa H. Alturaihy3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Aim: The present study aims to determine whether the level of serum interleukin -17 and IL-17 receptors (IL-17A) gene variant increases or decreases susceptibility to Allergic Rhinitis. Method: In this case-controlstudy fifty patients with rhinitis and fifty apparently healthy persons as a control in Babylon province /Iraq were enrolled in this study. Results: the results of this study were shown significant difference infrequency of IL-17 A (rs2275913) A>G polymorphism between Rhinitis patients and controls .Also , therewere significant difference in frequency of IL-17A (rs 2275913) between rhinitis patients and controls andthere were significant increase in patient compared with control. Conclusion: The bpresent study suggeststhat patients with AA allele for IL-17A (rs2275913) have increased susceptibility to rhinitis compared withGG allele , Also the present study suggests that IL-17A (rs2275913) is considered risk factor for AllergicRhinitis. This study suggests that the level of IL-17 patients with rhinitis highly significant compared withhealthy.